Models of care for the delivery of secondary fracture prevention after hip fracture: a health service cost, clinical outcomes and cost-effectiveness study within a region of England - Andrew Judge; M Kassim Javaid; José Leal; Samuel Hawley; Sarah Drew; Sally Sheard; Daniel Prieto-Alhambra; Rachael Gooberman-Hill; Janet Lippett; Andrew Farmer; Nigel Arden; Alastair Gray; et al. (National Institute for Health Research, 2016)
Background: Professional bodies have produced comprehensive guidance about the management of hip fracture. They recommend orthogeriatric services focusing on achieving optimal recovery, and fracture liaison services (FLSs) focusing on secondary fracture prevention. Despite such guidelines being in place, there is significant variation in how services are structured and organised between hospitals. Objectives: To establish the clinical effectiveness and cost-effectiveness of changes to the delivery of secondary fracture prevention services, and to identify barriers and facilitators to changes. Design: A service evaluation to identify each hospital's current models of care and changes in service delivery. A qualitative study to identify barriers and facilitators to change. Health economics analysis to establish NHS costs and cost-effectiveness. A natural experimental study to determine clinical effectiveness of changes to a hospital's model of care. Setting: Eleven acute hospitals in a region of England. Participants: Qualitative study - 43 health professionals working in fracture prevention services in secondary care. Interventions: Changes made to secondary fracture prevention services at each hospital between 2003 and 2012. Main outcome measures: The primary outcome is secondary hip fracture. Secondary outcomes include mortality, non-hip fragility fracture and the overall rate of hip fracture. Data sources: Clinical effectiveness/cost-effectiveness analyses - primary hip fracture patients identified from (1) Hospital Episode Statistics (2003-13, n = 33,152); and (2) Clinical Practice Research Datalink (1999-2013, n = 11,243). Results: Service evaluation - there was significant variation in the organisation of secondary fracture prevention services, including staffing levels, type of service model (consultant vs. nurse led) and underlying processes. Qualitative - fracture prevention co-ordinators gave multidisciplinary health professionals capacity to work together, but communication with general practitioners was challenging. The intervention was easily integrated into practice but some participants felt that implementation was undermined by under-resourced services. Making business cases for a service was particularly challenging. Natural experiment - the impact of introducing an orthogeriatrician on 30-day and 1-year mortality was hazard ratio (HR) 0.73 [95% confidence interval (CI) 0.65 to 0.82] and HR 0.81 (95% CI 0.75 to 0.87), respectively. Thirty-day and 1-year mortality were likewise reduced following the introduction or expansion of a FLS: HR 0.80 (95% CI 0.71 to 0.91) and HR 0.84 (95% CI 0.77 to 0.93), respectively. There was no significant impact on time to secondary hip fracture. Health economics - the annual cost in the year of hip fracture was estimated at £10,964 (95% CI £10,767 to £11,161) higher than the previous year. The annual cost associated with all incident hip fractures in the UK among those aged ≥ 50 years (n = 79,243) was estimated at £1215M. At a £30,000 per quality-adjusted life-year threshold, the most cost-effective model was introducing an orthogeriatrician. Conclusion: In hip fracture patients, orthogeriatrician and nurse-led FLS models are associated with reductions in mortality rates and are cost-effective, the orthogeriatrician model being the most cost-effective. There was no evidence for a reduction in second hip fracture. Qualitative data suggest that weaknesses lie in treatment adherence/monitoring, a possible reason for the lack of effectiveness on second hip fracture outcome. The effectiveness on non-hip fracture outcomes remains unanswered. Future work: Reliable estimates of health state utility values for patients with hip and non-hip fractures are required to reduce uncertainty in health economic models. A clinical trial is needed to assess the clinical effectiveness and cost-effectiveness of a FLS for non-hip fracture patients. Funding: The National Institute for Health Research (NIHR) Health Services and Delivery Research programme and the NIHR Musculoskeletal Biomedical Research Unit, University of Oxford.